Cosmic ray acceleration of cool clouds in the circumgalactic medium. Issue 1 (25th July 2019) - Wiener, Joshua; Zweibel, Ellen G; Ruszkowski, Mateusz
ABSTRACT: We investigate a mechanism for accelerating cool (10 4 K) clouds in the circumgalactic medium (CGM) with cosmic rays (CRs), possibly explaining some characteristics of observed high-velocity clouds (HVCs). Enforcing CRs to stream down their pressure gradient into a region of slow streaming speed results in significant build-up of CR pressure which can accelerate the CGM. We present the results of the first two-dimensional magnetohydrodynamic (MHD) simulations of such 'CR bottlenecks, ' expanding on simpler simulations in 1D. Although much more investigation is required, we find two main results. First, radiative cooling in the interfaces of these clouds is sufficient to keep the cloud intact to CR wave heating. Secondly, cloud acceleration depends almost linearly with the injected CR flux at low values (comparable to that expected from a Milky Way-like star formation rate), but scales sublinearly at higher CR fluxes in 1D simulations. 2D simulations show hints of sublinear dependence at high CR fluxes but are consistent with pure linear dependence up to the CR fluxes tested. It may therefore be plausible to accelerate cool clouds in the CGM to speeds of hundreds of km s −1 .